Vitamin B12 deficiency and impaired expression of amnionless during aging. Issue 1 (21st November 2017) - Pannérec, Alice; Migliavacca, Eugenia; De Castro, Antonio; Michaud, Joris; Karaz, Sonia; Goulet, Laurence; Rezzi, Serge; Ng, Tze Pin; Bosco, Nabil; Larbi, Anis; Feige, Jerome N.
Abstract: Background: Physical frailty and loss of mobility in elderly individuals lead to reduced independence, quality of life, and increased mortality. Vitamin B12 deficiency has been linked to several age‐related chronic diseases, including in the musculo‐skeletal system, where vitamin B12 deficiency is generally believed to be linked to poor nutritional intake. In the present study, we asked whether aging and frailty associate with altered vitamin B12 homeostasis in humans and investigated the underlying molecular mechanisms using preclinical models. Methods: We analysed a subset of the Singapore Longitudinal Aging Study and stratified 238 participants based on age and Fried frailty criteria. Levels of methyl‐malonic acid (MMA), a marker for vitamin B12 deficiency, and amnionless, the vitamin B12 co‐receptor that anchors the vitamin B12 transport complex to the membrane of epithelial cells, were measured in plasma. In addition, vitamin B12 levels and the molecular mechanisms of vitamin B12 uptake and excretion were analysed in ileum, kidney, liver, and blood using a rat model of natural aging where nutritional intake is fully controlled. Results: We demonstrate that aging and frailty are associated with a higher prevalence of functional vitamin B12 deficiency that can be detected by increased levels of MMA in blood (ρ = 0.25; P = 0.00013). The decline in circulating vitamin B12 levels is recapitulated in a rat model of natural aging where food composition and intake are stable. At the molecular level, these perturbations involve altered expression of amnionless in the ileum and kidney. Interestingly, we demonstrate that amnionless can be detected in serum where its levels increase during aging in both rodents and human ( P = 3.3e‐07 and 9.2e‐07, respectively). Blood amnionless levels negatively correlate with vitamin B12 in rats (r 2 = 0.305; P = 0.0042) and positively correlate with the vitamin B12 deficiency marker MMA in humans (ρ = 0.22; P = 0.00068). Conclusions: Our results demonstrate that aging and frailty cause intrinsic vitamin B12 deficiencies, which can occur independently of nutritional intake. Mechanistically, vitamin B12 deficiency involves the physio‐pathological decline of both the intestinal uptake and the renal reabsorption system for vitamin B12. Finally, amnionless is a novel biomarker which can detect perturbed vitamin B12 bioavailability during aging and physical frailty.